Isolation and Elucidation Structure of the Chemical Component from Ethyl Acetate Subfraction of Kelakai Stems (Stenochlaena palustris) - Pardede, Antoni; Wardhani, Raden Roro Ariessanty Alicia Kusuma (Jurnal Riset Kimia, 2025)
Kelakai (Stenochlaena palustris) belongs to the Blechnaceae family and offers numerous health benefits due to its chemical components. The isolation and structure elucidation of the chemical components from the ethyl acetate subfraction of the kelakai stems (Stenochlaena palustris) have been carried out. The isolation process began with the preadsorption of 241 mg of the E5.6 subfraction, which was then subjected to separation and purification using column chromatography. Three solvent combinations were used in the process: (chloroform 100%, chloroform: methanol (9:1), and chloroform: methanol (8:2)). The choice of solvent was based on the stain patterns observed in thin-layer chromatography (TLC). The chemical component was successfully isolated after chromatography, resulting in a white needle crystal weighing 15.2 mg and a single spot on the TLC, which was monitored using ultraviolet light at a wavelength of 254 nm. The structure of the chemical component was elucidated using 1H-NMR and 13C-NMR spectra, and comparison with literature data confirmed that the isolated compound from the ethyl acetate subfraction of the kelakai stems is succinic acid.